Pengaruh Sharing Pengetahuan Budidaya Rumput Laut Terhadap Pendapatan Petani Rumput Laut di Dusun Tolebeng Kecamatan Penrang Kabupaten Wajo - Nashriah Akil; Misbahuddin; Ihsan Guntur; Imran Taufik; Abdullah (Jurnal Online Manajemen ELPEI, 2023)
This research was conducted in Wajo district using knowledge sharing as an effort to increase income for seaweed farming farmers, while the sample in this study was 39 people as objects as well as being the population of Tolebeng village, after testing the hypothesis and accepting it, it was continued with validity and reliability.The results of this study indicate that knowledge sharing has an effect on the level of income of the Tolebeng village community which has a significance below 0.5, which means that knowledge sharing has an effect on the income of the Tolebeng community.